Experimental Research on Damage Parameter of Concrete in Non-Uniform Stress Field - Deng, Aimin; Xu, Daoyuan (My University, 2011)
The damage variables of describing the material damage state should be chosen first when the research of concrete structures by use of theory of damage theory. The method of calculation of damage parameter by the measure of the change of the elastic modulus of concrete specimens is effectively. In this paper, the wedge splitting tests with double bearing of three groups of different initial crack lengths of concrete specimens were conducted, and the stress and the strain of the points with different distance from the initial crack tip measured and calculated, and the damage value with peak stress of the various points were calculated based on the stress-strain curves. From the results of the test, the damage parameter can be confirmed under the non-uniform stress field, and the initial crack length has some influence on the damage parameter, and the longer the initial crack length and the greater the damage parameter
Keywords: Non-Uniform Stress Field; Wedge Splitting Experiment; Damage Parameter; Crack Length